Electrocardiographic identification of the culprit coronary artery in acute non-ST-elevation myocardial infarction: predictive value of N-wave and T-wave precordial instability. Issue 7 (November 2020) - Rostoff, Pawel; Wisniewski, Pawel; Gajos, Grzegorz; Konduracka, Ewa; Nessler, Jadwiga; Kruszelnicka, Olga
Abstract : Background: Recently, novel ischemic electrocardiographic changes have been described, which may be clinically significant in the identification of the culprit coronary vessel in patients with non-ST-elevation myocardial infarction (NSTEMI). We sought to determine the predictive value of N-wave, T-wave precordial instability, de-Winter ST/T-wave complex, and inferolateral myocardial infarction in the identification of the culprit artery in patients with NSTEMI referred for early invasive (<24 h) treatment. Methods: A total of 148 patients with NSTEMI, aged 40–91 years, were enrolled from a cohort of 510 consecutive NSTEMI subjects, hospitalized in our center in 2015–2017. Results: Of the evaluated ischemic ECG changes, the most common finding in patients with culprit left circumflex (LCx)/obtuse marginal artery or right coronary artery was T-wave precordial instability (28.3 and 13.5%, respectively), whereas in individuals with culprit left anterior descending/diagonal artery, T-wave precordial instability and N-wave in leads II, III or aVF occurred equally often (16.0%). A significant relationship was found between the occurrence of N-wave in inferolateral leads and culprit LCx/obtuse marginal. In multivariable analysis, N-wave in lead aVL [odds ratio (OR) 2.10; 95% confidence interval (CI), 1.15–3.81], and T-wave precordial instability (OR 1.56; 95% CI, 1.02–2.41) were independent predictors of culprit LCx/obtuse marginal. The accuracy of N-wave in lead aVL in predicting the culprit LCx/obtuse marginal was 73.9% and was higher than the accuracy of T-wave precordial instability, which was 69.1%. Conclusions: In patients with NSTEMI referred for early invasive treatment, the presence of N-wave or T-wave precordial instability may be of greater clinical importance in the prediction of culprit LCx/obtuse marginal than classic ischemic changes. Abstract : Supplemental Digital Content is available in the text.